TMEM207 hinders the tumour suppressor function of WWOX in oral squamous cell carcinoma. Issue 2 (22nd November 2017) - Bunai, Katsuaki; Okubo, Hiroshi; Hano, Kimika; Inoue, Keisuke; Kito, Yusuke; Saigo, Chiemi; Shibata, Toshiyuki; Takeuchi, Tamotsu
Abstract: The WW domain‐containing oxidoreductase (WWOX) functions as a tumour suppressor in oral carcinogenesis. As aberrant TMEM207 expression may lead to tumour progression by hampering the tumour suppressor function of WWOX in various cancers, we explored the expression and pathobiological properties of TMEM207, focusing on the WWOX‐mediated regulation of the HIF‐1α pathway in oral squamous cell carcinoma (OSCC). TMEM207 immunoreactivity was detected in 40 of 90 OSCC samples but not in neighbouring non‐tumorous epithelial tissues. Moreover, TMEM207 expression was significantly correlated with lymph node metastasis and poor prognosis. An in situ proximal ligation assay demonstrated the colocalization of TMEM207 and WWOX in invasive OSCC cells, especially glycogen‐rich ones. Enforced expression of TMEM207 abrogated the binding of WWOX to HIF‐1α, increased HIF‐1α and GLUT‐1 expression, even under normoxic conditions, and promoted tumour growth in a xenoplant assay using SAS tongue squamous cancer cells. In contrast, TMEM207 knockdown decreased GLUT‐1 expression in two OSCC cell lines. As a whole, our findings indicate that the aberrant expression of TMEM207 contributes to tumour progression in OSCC, possibly via promoting aerobic glycolysis.